Exploring of Coronilla varia L. extracts as a source of high-value natural agents: Chemical profiles and biological connections - Yerlikaya, Serife; Baloglu, Mehmet Cengiz; Altunoglu, Yasemin Celik; Diuzheva, Alina; Jekő, József; Cziáky, Zoltán; Zengin, Gokhan (Elsevier BV, 2021)
Abstract Pharmacological studies have indicated that flavonoids are crucial compounds to eliminate drug resistance. In this report, the activity of ethyl acetate (EAE), methanol (ME) and water (WE) extracts of Coronilla varia L. on antioxidant and enzyme inhibitory activities, DNA protective effects, antiproliferative activities, apoptotic; autophagic and telomerase gene activity analysis in breast cancer cells and inhibitory effects on cell migration ability of malignant breast cancer cells were examined. In addition, HPLC-MS-MS was used for detection of chemical profiles of all extracts. Results showed that the highest concentration of the bioactive components was detected in EAE (50.86 mg GAE/g for phenolics and 25.66 mg RE/g for flavonoid). Also, EAE displayed significant antioxidant properties in radical scavenging and reducing power assays. Regarding enzyme inhibitory effects, EAE and ME were more active than WE. Some significant compounds such as, vitamin B5, riboflavin, citric acid, and isoflavonoid derivate – medicarpin, noscapine were detected only in WE. Apigenin was determined in all extracts. WE indicated the most shield effect on pDNA against oxidative damage. Half-maximal inhibitory concentrations of extracts on breast cancer cells were calculated with MTT cell viability test. Bax gene was up-regulated and anti-apoptotic gene known as Bcl-2 was down-regulated on MDA-MB-231 cells after treated with WE. TERT-1 gene was down-regulated after treated with EAE and ME for MDA-MB-231 and MCF-7 cells, respectively. Cell migration ability of both MDA-MB-231 and MCF-7 cells was prevented with EAE and ME. A more effective treatment strategy can be applied by combining these extracts with commercial chemotherapy drugs which cause apoptosis and cell migration inhibition in vitro.
Keywords: 3. Good health